Analysis of Green Hospital Implementation in the Integrated Emergency Room Building Construction Project of RSUD K.R.M.T Wongsonegoro Semarang Based on Green Construction Site Index - Firmawan, Ferry; Purwanto, Purwanto; Rahmawati, Diah (Universitas Jember, 2024)
Construction activities have positive and negative impacts, one of the negative impacts is the generation of construction waste. As construction projects develop, waste generation also increases. As an effort to realize the concept of sustainable development in the health sector, the Directorate General of Health Services issued Guidelines for Environmentally Friendly Hospital (Green Hospital) in 2018. However, these guidelines do not contain guidelines for the implementation aspects of building construction. Therefore, the purpose of this study was to identify the factors, criteria, and indicators in the preparation of instruments for assessing aspects of the implementation of Green Hospital construction, and to analyze the results of the assessment. This research is qualitative using descriptive analysis method. The research results obtained 50 factors, 10 criteria and 3 indicators arranged in an assessment instrument called